Competencies of process managers (Journal of Universal Excellence, 2026)
Research Question (RQ): Effectiveness of managers differs in implementation of the process approach. Which competencies affect performance effectiveness of managers in the process approach?Purpose: The aim of the research is to specify a set of competencies which affect performance effectiveness of managers in the process approach.Method: The theoretical part examines the current state and terminology from the field of processes and competencies. The empirical part is based on a quantitative research. An online survey questionnaire was used for data collection. The survey was conducted among auditors of management systems worldwide.Results: The research indicates that there are significant differences between influences of different competencies on performance effectiveness of managers in the process approach. The studied competencies are presented in an array from the most to the least influential.Organization: The research directly affects the development of the HR function in organizations in practice. It enables an easier and more oriented personnel selection process and development of managers in the field of process performance.Society: The research enables easier orientation in competencies development that can improve the social order as well as social responsibility and the environment indirectly.Originality: The research originally offers a set of competencies that are relevant to process management.Limitations/Future Research: The research is restricted to the population of auditors. Future studies could examine the research question from a point of view of other professional groups.
Keywords: competencies; personal traits; process approach; business process management; management